NEOTYPIFICATION OF THE NAMES TARENNA CANARICA AND T. NILAGIRICA (RUBIACEAE) FROM THE WESTERN GHATS - Nair, Maya Sukumaran; Konickal Mambetta Prabhukumar; Sunilkumar Trivikraman Pillai (Phytotaxa, 2023)
N/A